(3GdJUajI Yf GdehGfY GdegdcI GdeQhjIs - (3eMeO Hf GdMSf GdOjdej,J (B711 (3g` s ((3TQja YHO Gddg GdYeQi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Od Ydi GdgjFI HEHOGY CeG HYO aGYde Cf Yf SfI GdMQU hGdZadI , hMH GdOfjG jYei hjUe , hGdefJHgjf Yf QbGO GdghG hGdTghI hGdfGS fjGe , aEPG eGJhG EfJHghG s
(3BNQgG (B:s
(3ceG bGd (B: ( (3dGZhjfge CLeYjf EdG YHGOc efge GdeNdUjf hEPG YXe GdeWdhH hGdMeO ddg Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ HYfGjI eMeO Hf MSjf TQja eGdcg s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3GdJUha hGdBOGH GdTQYjIs